Superoxide dismutase activities of spermatozoa and seminal plasma are not correlated with male infertility - Hsieh, Yao‐Yuan (J Clin Lab Anal, 2002)
Abnormal reactive oxygen species (ROS) production is associated with defective sperm function. Superoxide dismutase (SOD) is related with the scavenging of seminal ROS. We aimed to determine the effect of SOD activities of spermatozoa and seminal plasma on sperm quality. Semen samples from infertile couples who consented to the analyses were divided into two groups: 1) normospermia (n = 20); and 2) oligoasthenozoospermia (n = 31). The SOD activities of the spermatozoa and seminal plasma were measured by determining the inhibition of pyrogallol autoxidation. The SOD activities of spermatozoa and seminal plasma in both groups were compared. The relationships between the SOD activities and the sperm qualities were determined. We noted that SOD activities of sperm/seminal plasma in both groups were nonsignificantly different (group 1 vs. 2 = 0.77 ± 0.33/0.84 ± 0.40 U/mg protein for sperm, and 0.66 ± and 0.36/0.83 ± 0.47 U/ml for seminal plasma). SOD activities of sperm/seminal plasma were positively but nonsignificantly correlated with the sperm motility (SOD of sperm = 0.0008 × motility + 0.67; SOD of seminal plasma = 0.0006 × motility + 0.81) and concentration (SOD of sperm = 0.0006 × concentration + 0.67; SOD of seminal plasma = 0.0021 × concentration + 0.73). We concluded that SOD activities of sperm and seminal plasma were nonsignificantly correlated with the seminal quality. It appears that the SOD survey is not a useful tool for determining sperm fertilization potential. J. Clin. Lab. Anal. 16:127–131, 2002. © 2002 Wiley‐Liss, Inc.